2016
DOI: 10.1007/s10653-016-9872-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure factors of cadmium for residents in an abandoned metal mine area in Korea

Abstract: This study evaluated blood and urine cadmium (Cd) levels and human exposure factors for residents in an abandoned metal mine in Korea. We collected blood, urine, soil, water, and rice grain samples to analyze Cd concentrations and analyzed heavy metal concentration patterns in soil. We estimated the major exposure factor of Cd through non-carcinogenic risk assessment depending on exposure routes. The blood Cd concentration in the case group was 5.33 μg/L (geometric mean), significantly higher than that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
6
3
Order By: Relevance
“…The Residents Health Effect Survey was conducted in 2014 in the HEAMM area of this study; the geometric means of blood and urinary Cd in local residents were 5.33 and 5.31 µg/L, respectively, which were higher than those of this study 23 . In this survey, the geometric means of blood and urinary Cd in the residents of the HEAMM area were 1.93 µg/L and 2.46 µg/L, respectively, representing a decrease from 2014 but remaining at a high level.…”
Section: Discussioncontrasting
confidence: 58%
“…The Residents Health Effect Survey was conducted in 2014 in the HEAMM area of this study; the geometric means of blood and urinary Cd in local residents were 5.33 and 5.31 µg/L, respectively, which were higher than those of this study 23 . In this survey, the geometric means of blood and urinary Cd in the residents of the HEAMM area were 1.93 µg/L and 2.46 µg/L, respectively, representing a decrease from 2014 but remaining at a high level.…”
Section: Discussioncontrasting
confidence: 58%
“…It can be used as a pollution source tracking method in other regions using the analysis of Pb and As concentrations, environmental behaviors and the analysis of stable Pb isotope ratio applied to this study (Choi et al 2007; Yoo et al 2014; Ahn et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although the leaching behaviors of metals in tailing sample were investigated for the remediation of heavy metal soil contamination caused by mine tailing, generally because the metal contents do not exceed 0.1% in the contaminated soils near the abandoned mines in Korea, 1,2,13) the leaching tests were performed with low pulp density. The effects of pulp density (0.25%1%) on the leaching efficiency of metals were investigated in 1 M citrate at 400 rpm and 90°C with 3 h leaching time and 1 M Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…There are 2089 abandoned metal mines in South Korea, and it has been reported that about 60% (1268) abandoned metal mines have caused mine hazards such as soil contamination. 1) Thus, tailings in the abandoned mines have become one representative source of soil metal contamination, and there are increasing concerns about heavy metal soil contamination in the vicinity of the abandoned mines. 2) Heavy metals should be removed from soil because they are not decomposed naturally in the soil.…”
Section: Introductionmentioning
confidence: 99%